The Correlation Of Education And Income Level Relations Family With The Utilization Of Health Services: HUBUNGAN TINGKAT PENDIDIKAN DAN PENDAPATAN KELUARGA DENGAN PEMANFAATAN PELAYANAN KESEHATAN - Triana Putri, Sasni; Nurjaman, Deden; MP, Benny; Laia, Julianto; Honest, Irianto; Yunita; Rizka; Rizki, Eni; Adhie, Fajar; Fitrianingsih, Nining (Program Studi S1 Ilmu Keperawatan dan Ners IKBIS Surabaya, 2025)
Background: Puskesmas is a health service facility that organizes public health efforts and first-level individual health efforts by prioritizing promotive and preventive efforts to achieve the highest degree of health in its working area. Public health efforts include essential public health efforts and development health efforts. Efforts to consider health service needs. Objective: To determine the relationship between education level and family income with health service utilization. Methods: This research is correlational analytic with a cross sectional approach. The population in this study were 200 people, the number of samples in this study amounted to 133 respondents with the Random Sampling technique. The results of the study were tested with the Kendall tau statistical test with a significance of α = <0.05 with the SPSS 25 program. This research was conducted at the Cimandala Health Center, Bogor Regency. Results: Based on the results of the study obtained a p value of 0.000 <0.05, which means that there is a relationship between education level and utilization of health services at the Cimandala Health Center, Bogor Regency (Ho is rejected and Ha is accepted). And the results of the study also obtained a p value of 0.437> 0.05 which means that there is no relationship between the level of education on the utilization of health services at the Cimandala Health Center, Bogor Regency (Ho is accepted and Ha is rejected). Conclusion: The results of this study can provide an overview of the level of education and family income on the utilization of health services at the Cimandala Health Center, so that it can be a reference for improving good performance in the quality of service.